Potassium ion coordination and ionic transport in Alginate–PVA polymer electrolyte - Wahab, N.A; Mohd. Ali, Noor Saadiah; Ghazali, N.M.; Aoki, K.; Nagao, Yuki; Mazuki, N.F.; Samsudin, A. S. (Elsevier, 2025)
Solid biopolymer electrolyte (SBPE) systems based on alginate–polyvinyl alcohol (Al–PVA) doped with varying contents of potassium carbonate (K2CO3) were successfully developed using a solution casting technique. Structural analysis via FTIR and XPS confirmed strong interactions between K+ ions and the functional groups of the biopolymer blend. XRD results revealed reduced crystallinity with salt incorporation, indicating enhanced amorphousness favorable for ion transport. Thermal analysis using TGA and DSC showed improved thermal stability and segmental mobility with increasing K2CO3 content. Impedance spectroscopy indicated a notable drop in bulk resistance with optimal conductivity of 1.31 × 10−5 S cm−1 achieved at 12 wt% K2CO3. Temperature-dependent conductivity obeyed Arrhenius behavior, confirming thermally activated ion conduction. Transport parameters derived using the Arof–Noor model (number of charge carriers, mobility, and diffusion coefficient) exhibited trends consistent with conductivity results. These findings demonstrate the Al–PVA–K2CO3 SBPE system’s potential for energy-related applications requiring sustainable and thermally stable electrolytes.